Odpowiedź :
a)2x-3y x=-3 y=2
2*(-3)-3*2=-6-6=-12
b)3-6t-8w t=1/6 w=1/8
3-6*1/6-8*1/8=3-1-1=1
c)9k+8l k=0 l=0
9*0+8*0=0
d)m+p+mp m=1/2 p=1/3
1/2+1/3+(1/2)*(1/3)=5/6+1/6=1
e)(x+2)*(y-3) x=8 y=12
(8+2)*(12-3)=10*9=90
2*(-3)-3*2=-6-6=-12
b)3-6t-8w t=1/6 w=1/8
3-6*1/6-8*1/8=3-1-1=1
c)9k+8l k=0 l=0
9*0+8*0=0
d)m+p+mp m=1/2 p=1/3
1/2+1/3+(1/2)*(1/3)=5/6+1/6=1
e)(x+2)*(y-3) x=8 y=12
(8+2)*(12-3)=10*9=90
5.
a)Fg=m*g
Fg=250kg*10m/s²
Fg=2500N
b)g=m/v
g=540kg/0,2m³
g=2700kg/m³
c)V=S/t
V=300km/48h
V=6,25km/h
d)a=v*t
a=0,04km/h*24h
a=0,96km/h²
6.
a)2x-3y=2*(-3)-3*2= -6-6= -12
b)3-6t-8w=3-6*⅙-8*⅛=3-1-1=1
c)9h+8l=9*0+8*0=0
d)m+p+mp=½+⅓+½*⅓=½+⅓+⅙=³/₆+²/₆+¹/₆=⁶/₆=1
e)(x+2)(y-3)=xy-3x+2y-6=8*12-3*8+2*12-6=96-24+24-6=90
a)Fg=m*g
Fg=250kg*10m/s²
Fg=2500N
b)g=m/v
g=540kg/0,2m³
g=2700kg/m³
c)V=S/t
V=300km/48h
V=6,25km/h
d)a=v*t
a=0,04km/h*24h
a=0,96km/h²
6.
a)2x-3y=2*(-3)-3*2= -6-6= -12
b)3-6t-8w=3-6*⅙-8*⅛=3-1-1=1
c)9h+8l=9*0+8*0=0
d)m+p+mp=½+⅓+½*⅓=½+⅓+⅙=³/₆+²/₆+¹/₆=⁶/₆=1
e)(x+2)(y-3)=xy-3x+2y-6=8*12-3*8+2*12-6=96-24+24-6=90